PUBLIC AGENCIES IN SERBIA Accidental error or bad intention - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
English term "agency" has appeared in the Serbian legal system after the political changes in 2000. At first, the Law on Ministries in 2004 created bodies of state administration under the name of the agency and administrative organizations and in 2005 has been passed the Law on Public Agencies, which provides agencies as autonomous entities that are not directly part of the state administration. In addition, in the last ten years in Serbia was created a whole range of subjects of different legal status under the name of the agency. It should be borne in mind that the organization and structure of public administration in Serbia are mostly based on the Germanic tradition and that Serbia has long used the German term for persons performing administrative activities: "Verwaltungsorgan". Without any objective need, in addition to traditional forms of bodies performing administrative activities in Serbia has been created a new form called the agency. This has only brought the confusion into by then relatively harmonized system of governance structures, where the name of the former administration and some other subjects changed to agencies and some new, who previously did not exist, have been also created. This has led to the growth of covert administration. Agency name is not unknown in the world and in the US is used since the 18th century. However, instead of the name in English is translated into Serbian language in an adapted way, as it corresponds to the traditional Serbian terminology, this accidental error later turned into a bad intention of creating an ever-larger number of entities called agency.